2018
DOI: 10.1177/0266666918767482
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technologies and access to maternal and child health information: Implications for sustainable development

Abstract: Maternal and child mortality pose a great challenge in developing nations notwithstanding the robust initiatives instituted at both the global and national levels to ameliorate it. This study is aimed at ascertaining women’s perception of the impact of information and communication technologies on access to maternal and child health information and its implication on sustainable development. The descriptive research design was adopted for the study. Purposive sampling technique was used in selecting University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Their study reveals that the use of ICT apparatuses, resources and services had a great impact on the research activities and work performance of research scholars. Ukachi and Anasi's (2019) study also reports the positive impact of ICT on women's access to material and child-health information. The study by Buarki et al (2011) points out that, in spite of having rich resources, there are many flaws in the ICT applications in the field of library science in Kuwait.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Their study reveals that the use of ICT apparatuses, resources and services had a great impact on the research activities and work performance of research scholars. Ukachi and Anasi's (2019) study also reports the positive impact of ICT on women's access to material and child-health information. The study by Buarki et al (2011) points out that, in spite of having rich resources, there are many flaws in the ICT applications in the field of library science in Kuwait.…”
Section: Literature Reviewmentioning
confidence: 95%
“…According to Mechael (9), innovations and development in the healthcare system are immensely needed in developing economies. Furthermore, the progress in healthcare applications also required the development from other disciplines such as education, engineering, computer science, psychology, and sociology to enhance the satisfaction level of patients from the health care system (10). Several studies reported the potential of ICT in delivering health-related facts and its contribution to organizing several vaccination programs in developing economies (11).…”
Section: Introductionmentioning
confidence: 99%
“…The indication is that women need health information to improve their health knowledge base and also be able to make informed decisions on things that affect their lives. Ukachi and Anasi (2018) also emphasized that health information is needed to reduce levels of uncertainty and enable people to take the right health decisions.…”
Section: Discussion Of Findingsmentioning
confidence: 99%